Bioactivity of the Protein Hydrolysates Obtained from the Most Abundant Crustacean Bycatch - Camargo, Tavani R. [UNESP]; Mantoan, Paulo [UNESP]; Ramos, Patrícia; Monserrat, José M.; Prentice, Carlos; Fernandes, Célio C. [UNESP]; Zambuzzi, Willian F. [UNESP]; Valenti, Wagner C. [UNESP] (Springer Nature, 2021)
The animals from bycatch of the shrimp fisheries can be a source of natural products and bioactive compounds. Thus, the present study aimed to evaluate the bioactivity of protein hydrolysates prepared from the two most abundant crabs from the bycatch of shrimp fisheries in Brazil (Callinectes ornatus and Hepatus pudibundus). Samples of C. ornatus and H. pudibundus were collected in the region of Ubatuba, State of São Paulo, Brazil. Muscles with small pieces of exoskeleton of both species were hydrolyzed using two enzymes, Alcalase 2.4 L® or Protamex®. The in vitro antioxidant capacity was analyzed used three methods: DPPH, sulfhydryl groups, and peroxyl radicals. Additionally, the cytotoxicity of the hydrolysates was investigated using pre-osteoblasts cells. The results showed that the degree of hydrolysis (DH) of H. pudibundus was superior to DH of C. ornatus using both enzymes and was higher when using the enzyme Alcalase 2.4 L® (32.0% ± 1.9). The analysis suggested that the hydrolysates have antioxidant activity. Besides that, no cytotoxic effect was observed on cell viability. Thus, protein hydrolysates of C. ornatus and H. pudibundus have bioactivity, which add value to these bycatch species and suggests their potential use as nutraceutical ingredient in the food industry. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Antioxidant activity; Cell viability; DPPH; Enzymatic hydrolysis